2017
DOI: 10.3390/ijms18081756
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 Performance in Histologic and Cytologic Assessment of Thyroid Nodules: A Systematic Review and Meta-Analysis

Abstract: The literature on Galectin-3 (Gal-3) was systematically reviewed to achieve more robust information on its histologic reliability in identifying thyroid cancers and on the concordance between Gal-3 test in histologic and cytologic samples. A computer search of the PubMed and Scopus databases was conducted by combinations of the terms thyroid and Gal-3. Initially, 545 articles were found and, after their critical review, 52 original papers were finally included. They reported 8172 nodules with histologic evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 74 publications
(99 reference statements)
0
23
0
Order By: Relevance
“…TIMP-1, acts as an inhibitor for MMP9 expression that is often co-expressed with this molecule in thyroid tumors and serves as a reliable surrogate marker for BRAF-mutated status and likely aggressiveness (41). Notably, TIMP-1 serves as a prominent PPI hub gene in the Cytoscape network built upon co-expression of TNFRSF12A and CHI3L1, along with LGALS3, a specific biomarker of well-differentiated thyroid carcinomas (42), CXCL16, which mediated the involvement of macrophages in the invasion of papillary TCs (43) and fibronectin, an EMT biomarker which promoted migration and invasion of papillary thyroid cancers (44).…”
Section: Multiple Linear Regression Mega-analysis Results Analysis Fomentioning
confidence: 99%
“…TIMP-1, acts as an inhibitor for MMP9 expression that is often co-expressed with this molecule in thyroid tumors and serves as a reliable surrogate marker for BRAF-mutated status and likely aggressiveness (41). Notably, TIMP-1 serves as a prominent PPI hub gene in the Cytoscape network built upon co-expression of TNFRSF12A and CHI3L1, along with LGALS3, a specific biomarker of well-differentiated thyroid carcinomas (42), CXCL16, which mediated the involvement of macrophages in the invasion of papillary TCs (43) and fibronectin, an EMT biomarker which promoted migration and invasion of papillary thyroid cancers (44).…”
Section: Multiple Linear Regression Mega-analysis Results Analysis Fomentioning
confidence: 99%
“…Alterations of the glycan profile in TCs have been observed in thyroid tissue sections and in thyroid cells cultured in vitro. Moreover, the expression of galectins specific for β-galactose or LacNAc disaccharide was altered in TCs [ 100 , 101 ].…”
Section: Glycosylation In Thyroid Pathologymentioning
confidence: 99%
“…Therefore, identifying parameters that may serve as potential markers of malignancy has a significant clinical value. Some of the molecular, cytological, ultrasound, and clinical studies investigated these parameters but yielded controversial results (7)(8)(9). Some recent studies reported that the microscopic histological examination of the core-needle biopsy (CNB) could diagnose a large number of uncertain thyroid nodules.…”
Section: Introductionmentioning
confidence: 99%